2010
DOI: 10.1071/pc110244
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of the Liberator? in reducing predation on wildlife by domestic cats

Abstract: We evaluated the effectiveness of the commercial collar-worn product the Liberator? in reducing the number of vertebrates pet cats bring home. Fifteen cats identified by their owners as hunters bringing home at least one prey animal per fortnight were included in the study, which was carried out in Perth, Western Australia over six weeks in November/December 2006 (southern hemisphere late spring/early summer). Each cat spent three weeks wearing a Liberator? and three weeks without it and the number of prey bro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A new Chilean law promoting responsible pet ownership was recently enacted ( Ministry of Health, 2017 ) and could be a first step towards regulating confinement by national legislation which was considered far from sufficient in 2014 by Bonacic & Abarca (2014) . Meanwhile, bells, electronic alarms, or colorful collar covers are an option for free-roaming cats to reduce depredation rates on wildlife ( Gordon, Matthaei & Van Heezik, 2010 ; Calver & Thomas, 2011 ; Willson, Okunlola & Novak, 2015 ), as well as advice on environmental enrichment techniques for indoor cats ( Rochlitz, 2005 ), outdoor enclosures, and leash training ( Hall et al, 2016 ). (5) Finally, an instrument such as this survey can reveal what problems with free-roaming pets exist; thus, it provides insight into impacts in the absence of biological studies or complementary to them (e.g., dogs interacting with rare and endemic mammals were only detected through interviews in Silva-Rodriguez & Sieving, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…A new Chilean law promoting responsible pet ownership was recently enacted ( Ministry of Health, 2017 ) and could be a first step towards regulating confinement by national legislation which was considered far from sufficient in 2014 by Bonacic & Abarca (2014) . Meanwhile, bells, electronic alarms, or colorful collar covers are an option for free-roaming cats to reduce depredation rates on wildlife ( Gordon, Matthaei & Van Heezik, 2010 ; Calver & Thomas, 2011 ; Willson, Okunlola & Novak, 2015 ), as well as advice on environmental enrichment techniques for indoor cats ( Rochlitz, 2005 ), outdoor enclosures, and leash training ( Hall et al, 2016 ). (5) Finally, an instrument such as this survey can reveal what problems with free-roaming pets exist; thus, it provides insight into impacts in the absence of biological studies or complementary to them (e.g., dogs interacting with rare and endemic mammals were only detected through interviews in Silva-Rodriguez & Sieving, 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Improved collar usage for cats may improve uptake of huntingdeterrent devices, such as bells, which have been demonstrated to reduce the hunting success of cats (Nelson et al 2005;Calver et al 2007;Gordon et al 2010). Regular use of collars with antipredation devices may mitigate the impact of cats on native and non-native fauna in New Zealand (Farnworth et al 2010a;Calver and Thomas 2011). Thomas et al (2012) reported that cat owners were less likely than non-cat owners to consider collar-mounted antipredation devices to be acceptable, which may explain why respondents to a New Zealand survey stated that of those cats wearing collars, only half of them had bells attached (Farnworth et al…”
Section: Introductionmentioning
confidence: 99%
“…One participant who was allowing their cat to roam unrestricted was using a bell and a cat bib on their cat in the hope of reducing their impact on wildlife. This is another contentious issue, with studies both supporting and rejecting the effectiveness of these methods [ 29 , 34 , 35 , 36 , 37 , 38 ]. In the push for the containment of pet cats, the use of curfews, and bells/bibs are two issues that need to be clarified (and communicated)—are they acceptable forms of management to help minimise the impacts on wildlife; what is their impact on the welfare of the cat; and what effect, if any, do they have on the other motivations for containing cats?…”
Section: Discussionmentioning
confidence: 99%